Tsunamis Case Studies and Recent Developments - Satake, Kenji; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
Twenty papers comprise a timely review of state-of-the-art tsunami research. Various approaches are taken to study tsunamis: field-surveys of recent tsunamis; analysis of tide-gauge records; numerical simulations of tsunami generation and propagation, tank experiments, and geological studies of tsunami deposits. The papers are also divided into two parts: case studies and recent developments. The first part reports on tsunamis generated by volcanic eruptions and earthquakes around the Pacific Ocean. The papers include summaries of post-tsunami surveys in the last decade; reports on the two tsunamis in 2003 which occurred in Fiordland in New Zealand and Tokachi-oki, Japan; reports and mechanism of tsunamis from the 1994 Rabaul, 1883 Krakatau and 1741 Oshima-Oshima eruptions; resonance and delayed peaks observed on the Sanriku coast of northern Japan; studies of tsunami deposits in Japan and Russia used to infer paleotsunamis along the Kuril trench; estimation of tsunami energy along the Aleutian-Alaska and Canadian coast based on historical data. The second part reports recent developments in numerical computations, monitoring, and assessments of coastal hazards. The papers include assessments of future tsunami impacts, based on the past tsunami or marine survey data, for the Ecuador, Portuguese and Korean coasts; adjoint technique for waveform inversion of source parameters; experimental design to study underwater landslides; numerical and experimental studies to evaluate the effects of coastal vegetation and control forests on tsunamis; proposals of new tsunami monitoring techniques using acoustic waves and electromagnetic signals.
Case Studies -- 1992-2002: Perspective on a Decade of Post-Tsunami Surveys -- The Fiordland Earthquake and Tsunami, New Zealand, 21 August 2003 -- Timing and Scale of Tsunamis Caused by the 1994 Rabaul Eruption, East New Britain, Papua New Guinea -- Analysis of Tide-Gauge Records of the 1883 Krakatau Tsunami -- Model of Tsunami Generation by Collapse of Volcanic Eruption: The 1741 Oshima-Oshima Tsunami -- Tsunami Resonance Curve from Dominant Periods Observed in Bays of Northeastern Japan -- Delayed Peaks of Tsunami Waveforms at Miyako from Earthquakes East off Hokkaido -- Field Survey of the 2003 Tokachi-Oki Earthquake Tsunami and Simulation at the Ootsu Harbor Located at the Pacific Coast of Hokkaido, Japan -- Variability Among Tsunami Sources in the 17th-21st Centuries Along the Soutehrn Kuril Trench -- Holocene Tsunami Traces on Kunashir Island, Kurile Subduction Zone -- Distribution of Cumulative Tsunami Energy from Alaska-Aleutians to Western Canada -- Recent Developments -- Mapping the Possible Tsunami Hazard as the First Step Towards a Tsunami Resistant Community in Esmeraldas, Ecuador -- Progresses in the Assessment of Tsunami Genesis and Impacts around the Portuguese Coasts -- Quick Tsunami Forecasting Based on Database -- Adjoint Inversion of the Source Parameters of Near-Shore Tsunamigenic Earthquakes -- Experimental Design for Solid Block and Granular Submarine Landslides: A Unified Approach -- Effects of Coastal Forest on Tsunami Hazard Mitigation - A Preliminary Investigation -- Fluid Force on Vegetation Due to Tsunami Flow on a Sand Spit -- Hydro-Acoustic Monitoring on the Kamchatka Shelf: A Possibility of Early Location of Oceanic Earthquake and Local Tsunami Warning -- Electromagnetic Tsunami Monitoring: Theory and Recommendations.
Keywords: PHYSICAL GEOGRAPHY; OCEANOGRAPHY; GEOGRAPHY; CIVIL ENGINEERING; ENVIRONMENTAL MANAGEMENT; GEOSCIENCES; OCEANOGRAPHY; CIVIL ENGINEERING; GEOPHYSICS/GEODESY.; GEOGRAPHY (GENERAL).; ENVIRONMENTAL MANAGEMENT